1998
DOI: 10.1177/030802269806100513
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Occupational Therapy Practitioners in Mental Health

Abstract: As part of the College of Occupational Therapists' Mental Health Project, a survey of occupational therapists practising in mental health in the United Kingdom was conducted. A questionnaire was sent to 200 members of the Association of Occupational Therapists in Mental Health and achieved a 68.5% response rate. The majority of the 137 respondents were female, with Senior I staff between 20 and 30 years of age, who were unlikely to have worked in another area, forming the largest group. Although most had rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
74
5

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(97 citation statements)
references
References 11 publications
18
74
5
Order By: Relevance
“…These members of the profession are at higher risk of leaving their posts and potentially the profession. A situation the profession can ill afford (Craik et al, 1998b).…”
Section: Discussionmentioning
confidence: 99%
“…These members of the profession are at higher risk of leaving their posts and potentially the profession. A situation the profession can ill afford (Craik et al, 1998b).…”
Section: Discussionmentioning
confidence: 99%
“…Crucially there were no reported studies on service users' views of occupational therapy in acute psychiatric inpatient settings, despite the fact that a notable proportion of occupational therapists worked within this area (Craik, Chacksfield & Richards, 1998) However, the important contribution of occupational therapy within acute mental health in delivering quality and effective therapeutic input must not be dismissed. Both the Sainsbury Centre for Mental Health (SCMH) Report (1998) and the Department of Health (2001) document support this perspective.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The therapeutic use of leisure is a frequent intervention by mental health occupational therapists (Craik et al 1998). In a questionnaire evaluation of 34 computing sessions completed by 19 clients and 4 staff, Di Bona and Boyle (2001) found that games were the second most common activity (18%) and suggested that computer games and videogames were seen as useful tools for enhancing leisure occupation.…”
Section: Videogame Research Within Mental Health Settingsmentioning
confidence: 99%